Perancangan Desain Website Cetak.id Menggunakan Metode User Centered Design (UCD) - Ridwan, Muhammad; Maysanjaya, I Made Dendi; Pratiwi, Putu Yudia (Jurnal Pseudocode, 2024)
Printing is currently a necessity for society in printing documents, printing banners, brochures, posters and so on. However, in its implementation there are problems such as customers canceling orders unilaterally, long queues at printing places, miscommunication between customers and service providers, and poor queue management. Based on these problems, there is a need for a system to manage the printing process. Before system development there needs to be a design to ensure that the system being built meets user needs. The research created a prototype design for ordering a print service called Cetak.id using the User Centered Design (UCD) method. At the testing stage, 2 tests were carried out by testing 5 aspects of usability. The first test was carried out based on the results of the design made, while the second test was carried out based on the results of the improved design from the first test. Based on the first and second tests for each group of users from service providers and service seekers, the results obtained were that the Learnability aspect had increased by 12% and 8%, respectively, the Efficiency aspect had increased by 0.043 goals/second and 0.023 goals/second, respectively. in the Memorability aspect there was an increase of 16.14% and 19.85% respectively, in the Error aspect there was a decrease of 0.04 and 0.09 respectively, while in the Satisfaction aspect using the Questionnaire for User Interaction Satisfaction (QUIS) each experienced an increase in indicator 1 of 0.64 and 0.72, indicator 2 is 0.7 and 0.3, indicator 3 is 0.83 and 0.73, indicator 4 is 0.87 and 0.7, and indicator 5 is 0.84 and 0.68. Keywords: Cetak.id, UCD, Usability Testing, QUIS